New Concept of Cultivation Using Limited Strip-Tillage with Strip Shallow Irrigation - Yazid Ismi Intara; A Sapei; Erizal Erizal; Namaken E. S; M. Bintoro Joefrie (Chemical Engineering Diponegoro University, 2014)
Dry land is one of land resources which potentially used for food crop cultivation, especially in the areas which have light to medium technical obstacles. The development of technology to improve soil quality in marginal lands to be productive lands is still widely open for agricultural development in Indonesia. Rooting medium quality can be improved by changing soil tillage method and observing the proper crop irrigation technology. It can be the solution for crop cultivation in clay loam soil. This study aimed to obtain water movement model in a minimally-tilled clay soil with strip shallow irrigation. The concept is limited soil-tillage with strip shallow irrigation method, water supply technique, and crop water requirement. Method used in this study includes developing water movement model (software development) in a minimally-tilled clay soil with subsurface irrigation. In the final stages, research also conducted water movement analysis testing apparatus in the laboratory, field validation of the subsurface irrigation performance, and cultivation technique testing to chili pepper growth (Capsicum annuumL.). The development of water movement simulation on a limited strip-tillage with subsurface irrigation uses the concept to quantify the amount of water in the soil. The analysis of movement pattern was demonstrated on contour patterns. It showed that the wetting process can reach depth zone – 5 cm to the rooting zone. It was an important discovery on the development of minimum stripe tillage soil with subsurface irrigation. Specifically, it can be concluded that: the result of fitting by eyes to diffusivity graphic and water content obtained the required parameter values for soil physical properties. It was then simulated on horizontal water movement model on a minimum strip-tillage with strip shallow irrigation